Respuesta :
Step-by-step explanation:
in what form do you need this equation ?
I simply assume it is the slope-intercept form :
y = ax + b
"a" is the slope of the line, "b" is the y-value when x = 0 (the point where the line intercepts the y-axis).
the slope is the ratio
y coordinate difference / x coordinate difference
when going from one point on the line to another.
in our case let's go from (2, 4) to (4, 2), as I personally prefer to go from left to right.
x changes by +2 (from 2 to 4).
y changes by -2 (from 4 to 2).
the slope is then -2/+2 = -1.
that means we know half of the equation :
y = -x + b
to get "b" we use the coordinates of one of the points in this half finished equation. e.g. (2, 4) :
4 = -(2) + b = -2 + b
b = 6
and our equation is
y = -x + 6
The answer is x + y - 6 = 0 (General Form)
EXPLANATION:
the formula to find the equation of a line is:
y - y1 = m(x - x1)
First, we need to find the gradient of points (4,2) & (2,4).
m = y2 - y1/x2 - x1
now sub them in: m = 4-2/2-4 = 2/-2 = -1
therefore m = -1
now pick a point and sub it into the equation of a line ( y-y1=m(x-x1)).
I will pick (4,2).
y - 2 = -1(x - 4)
y - 2 = -x + 4
now move x and 4 to the left side as x must always be positive in general form.
x + y - 6 = 0
ye
EXPLANATION:
the formula to find the equation of a line is:
y - y1 = m(x - x1)
First, we need to find the gradient of points (4,2) & (2,4).
m = y2 - y1/x2 - x1
now sub them in: m = 4-2/2-4 = 2/-2 = -1
therefore m = -1
now pick a point and sub it into the equation of a line ( y-y1=m(x-x1)).
I will pick (4,2).
y - 2 = -1(x - 4)
y - 2 = -x + 4
now move x and 4 to the left side as x must always be positive in general form.
x + y - 6 = 0
ye